Evaluation for improving student outcomes : messages for quality assurance policies - (:unkn) unknown (Publications Office of the European Union, 2011)
"Improving the quality of European education and training systems is one of the pillars of Europe's strategy to become a smart, sustainable and inclusive economy by 2020. This publication aims to provide policy and decision-makers with recommendations to help them develop a culture of evaluation and continuous improvement in schools and training institutions in Europe. It highlights a number of key messages to promote external evaluation and self-assessment and ensure the quality of education and training provision. Recommendations in this publication are based on the discussions of two peer learning study visits for high level policy and decision-makers organised in Vilnius and Hamburg in 2010 and a workshop Cedefop organised in Bonn in February 2011 on enhancing quality on schools and VET institutions. The study visits programme organises approximately 20 visits each year allowing decision-makers and practitioners to identify practical examples of good practice and explore issues related to quality in education and vocational training with their peers from other European countries." (Hrsg., BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 6.2 Qualitätsmanagement/Qualitätssicherung; L 6.2.3 Evaluation; I 2.2 Europa; Schulische Berufsausbildung; Betriebliche Berufsausbildung; Qualitätssicherung; Evaluation; Europa